Bismuth-based materials for supercapacitor application - Tripathi, Babita; Gujjar, Surajbhan; Yahya, M. Z.A.; Noor, I. M.; Singh, Ram Chandra (John Wiley and Sons, 2025)
The demand for supercapacitors is highly increasing in the area of energy storage devices. In the last decade, researchers have explored such types of electrode materials, which contain high energy density, are electrochemically stable, are eco-friendly, and are economically usable. Various research has been based on metal-based nanocomposites, among which bismuth-based nanocomposites are highly recommended due to their multiferroic redox characteristics, charge-storage capacity, and nontoxic behavior. In this research communication, the authors discuss the importance of bismuth-based materials in the area of energy storage devices, the types of bismuth nanocomposite for supercapacitor applications, and their future scope in the area of energy storage applications.